Dog vs Strawberry - Buchet, Nelly; Zuill, Andrea (New York : Random House Studio, 2024)
When Dog is handed a strawberry from the fruit bowl, she sizes it up, dances around it, and decides she is going to race the Strawberry--and win.
Ages 3-7.
Grades K-1.
Keywords: Dogs -- Juvenile fiction; Strawberries -- Juvenile fiction; Racing -- Juvenile fiction; Dogs -- Fiction; Strawberries -- Fiction; Racing -- Fiction; Picture books